The dynamics of chromatin architecture in brain development and function. (April 2021) - Harabula, Izabela; Pombo, Ana
Abstract : The brain comprises many different cell types with specialized functions which respond and adapt to the continuously changing environment, through tight spatiotemporal regulation of gene expression. The three-dimentional (3D) organisation of the genome is increasingly recognized as a major feature of gene regulation in brain cells, for the activation, repression and poising of gene expression, and in coupling transcription with RNA processing and transport. Here, we discuss the importance of dynamic chromatin organisation in the developmental patterning of the brain, and its role in fine tuning brain activity and plasticity. A better understanding of how disease-associated mutations interfere with chromatin organisation and long-range gene regulation will help reveal the molecular mechanisms underlying complex neurodevelopmental and neuropsychiatric disorders.